Identification of GBN5 as a molecular biomarker of pan-cancer species by integrated multi-omics analysis - Qian Guo; Xinxin Zhong; Zihan Dang; Baiquan Zhang; Zixin Yang (Discover Oncology)
Abstract Introduction We conducted a panoramic analysis of GBN5 expression and prognosis in 33 cancers, aiming to deepen the systematic understanding of GBN5 in cancer. Materials and methods We employed a multi-omics approach, including transcriptomic, genomic, proteomic, single-cell cytomic, spatial transcriptomic, and genomic data, to explore the prognostic value and potential oncogenic mechanisms of GBN5 across pan-cancers from multiple perspectives. Results We found that GBN5 was differentially expressed in multiple tumors and showed early diagnostic value. Mutations, somatic copy number alterations, and DNA methylation lead to its aberrant expression. GBN5 expression is associated with many clinical features. GBN5 expression has been validated to be associated with many metabolic, metastatic, and immune-related pathways. We also demonstrated that GBN5 expression was significantly associated with immunomodulatory molecules and biomarkers of lymphocyte subpopulation infiltration. Methylation levels of GBN5 expression were significantly negatively correlated in a variety of tumors, and GBN5 missense mutations were the predominant SNP type in pan-cancer. In addition, GBN5 was positively correlated with multiple genomic scores, implying that higher GBN5 expression tends to imply that patients have higher chromosomal instability. More importantly, GBN5 has an important role in predicting drug sensitivity. We have also developed effective targeted drugs against GBN5. Conclusion GBN5 plays an important role in the genesis and progression of various tumors and is a potential tumor diagnostic and prognostic biomarker as well as an anti-cancer therapeutic target.